Prevalence, knowledge and factors associated with e-cigarette use among parents of secondary school children - Julie Doherty; Jenny Davison; Marian McLaughlin; Melanie Giles; Lynn Dunwoody; Claire McDowell; Sarah Butter; Elaine Wilmont; Ellen Simpson (Elsevier, 2022)
Objectives: Identify prevalence rates and attitudes towards e-cigarette use among parents to inform prevention strategies designed to reduce uptake in young people. Study design: A mixed methods sequential study guided by the Theory of Planned Behaviour. Methods: This research involved two phases. Phase one was an elicitation study using focus groups, interviews and open-ended questionnaires (N = 17) to elicit parental behavioural, normative, and control beliefs around e-cigarette use. Findings from phase 1 were used to inform a questionnaire administered to a sample of 612 parents in phase 2. The aim of phase 2 was to identify and explain factors that influence parental attitudes and motivations towards e-cigarette use. Parents were recruited through post-primary schools and were sent a link to an online survey. Results: Approximately 19% of parents had tried an e-cigarette, with 9% reporting current use. Sociodemographic variables, TPB constructs and knowledge of e-cigarettes, accounted for 43% and 60% of ever use and intention to use an e-cigarette, respectively. Intention, gender, age and free school meal entitlement were associated with ever use. Intention to use an e-cigarette was related to lower educational level, current smoking of traditional cigarettes, more positive attitudes, greater social pressure, having greater control over use and knowledge. Conclusions: Prevention strategies designed to reduce uptake in young people should raise awareness of the health risks of e-cigarette use, legislation and regulations and highlight the role parents play in encouraging young people to abstain from using an e-cigarette.